1997
DOI: 10.1177/00220345970760060801
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Self-reported Dental Anxiety in New Zealand Adolescents from Ages 15 to 18 Years

Abstract: Little is understood of the natural history of dental anxiety. The aim of this study was to examine three-year changes in self-reported dental anxiety among adolescent participants in the Dunedin Multidisciplinary Health and Development Study. Dental anxiety was estimated at ages 15 and 18 by means of the Corah Dental Anxiety Scale (DAS). A DAS score of 13+ defined high dental anxiety. Participants were assigned to one of four dental-anxiety study groups (Chronic, Incident, Remitted, or Never) on the basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 12 publications
2
38
1
2
Order By: Relevance
“…Thomson et al . did not find a different prevalence of DFA in their study population at age 15 compared with age 18, but when comparing DAS mean scores, the younger group scored higher 49 .…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Thomson et al . did not find a different prevalence of DFA in their study population at age 15 compared with age 18, but when comparing DAS mean scores, the younger group scored higher 49 .…”
Section: Resultsmentioning
confidence: 69%
“…Two studies did not find any differences 17,42 (one based on mean scores and one on prevalence). One study reported no differences in the total group, but higher scores on CFSS‐DS in boys in an older age group (9–11 years olds) 23 , and one study reported no differences in prevalence but higher mean scores on DAS in girls 49 .…”
Section: Resultsmentioning
confidence: 95%
“…Avoidance of general dental appointments because of fear is reported to range between 5.5% and 15.5% in different populations (5,7,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), indicating the importance of understanding the origin of a patient's fears so that appropriate management strategies may be implemented. The present study looks to understand the origins of dental fear in an ethnic diverse group of patients attending the Griffith University Dental Clinic.…”
Section: Clinical Research Discussionmentioning
confidence: 99%
“…Fortunately, dental fear sometimes remits but it may also persist or increase [3,16,17]. In the latter scenarios, psychological and practical problems during dental treatment may occur, not only for the patients but also for the dental health professionals.…”
Section: Introductionmentioning
confidence: 99%